Assessment in holistic learning - Zubairi, Ainol Madziah (2018)
This workshop is designed to provide an overview of holistic learning within the paradigm of outcome-based education. At the end of the workshop, participants are expected to be exposed to the principles behind OBE, the place of assessment in OBE and the principles behind quality assessment for holistic learning. The participants are also taken through a session to reflect on their current assessment practices in order to align to the CLOs that require a holistic assessment of student learning.